Social science reference services - Baxter, Pam M. (Haworth Press, 1995)
This new book examines the topics and issues important to information professionals and librarians-in-training who serve clientele using social science materials. Social Science Reference Services addresses reference services across the spectrum of the social sciences and embraces a multidisciplinary approach to providing both materials and services to users